Astragalus of Pondaungimys (Rodentia, Anomaluroidea) from the late middle Eocene Pondaung Formation, central Myanmar. Issue 6 (2nd November 2018) - Coster, Pauline M.; Soe, Aung Naing; Beard, K. Christopher; Chaimanee, Yaowalak; Sein, Chit; Lazzari, Vincent; Jaeger, Jean-Jacques
ABSTRACT: A well-preserved astragalus of the anomaluroid rodent Pondaungimys anomaluropsis is described from the late middle Eocene Pondaung Formation of central Myanmar. This specimen is the first postcranial element of a rodent from the Pondaung Formation and the oldest postcranial fossil currently known for Anomaluroidea. It illuminates plesiomorphous postcranial conditions in early anomaluroids and provides a basis for reconstructing the evolution of arboreal locomotion in this group of rodents. In contrast to those of living anomaluroids, the astragalus of Pondaungimys bears features indicating a less mobile ankle, specifically including a reduced range of plantarflexion at the upper ankle joint and a diminished capacity for inversion at the lower ankle joint. Its anatomy suggests that early anomaluroids were generalized quadrupeds, with intermediate arboreal adaptations between those of paramyids and modern anomaluroids. A cladistic analysis based on astragalar characters corroborates a basal position for Pondaungimys among anomaluroids. The phylogenetic signal derived from astragalar morphology is consistent with recent assessments of relationships among living anomaluroids based on craniodental characters and molecular data. Stem anomaluroids such as Pondaungimys apparently lacked the ability to glide, a locomotor pattern that is retained in extant Zenkerella .